2015
DOI: 10.1016/j.ygeno.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization, phylogenetic comparison and differential expression of the cyclic nucleotide-gated channels gene family in pear (Pyrus bretchneideri Rehd.)

Abstract: The cyclic nucleotide-gated channel (CNGC) family is involved in the uptake of various cations, such as Ca(2+), to regulate plant growth and respond to biotic and abiotic stresses. However, there is far less information about this family in woody plants such as pear. Here, we provided a genome-wide identification and analysis of the CNGC gene family in pear. Phylogenetic analysis showed that the 21 pear CNGC genes could be divided into five groups (I, II, III, IVA and IVB). The majority of gene duplications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Ca 2+ signalling is a key topic in cell signalling research (Spalding and Harper 2011;Edel and Kudla 2014) and Eukaryotic cells generate cytosolic Ca 2+ signals via Ca 2+ -permeable channels. In plants, cyclic nucleotidegated cation (CNGC) channels (Frietsch et al 2007;Gao et al 2014Gao et al , 2016Chen et al 2015b), glutamate-like receptor (GLR) calcium channels (Michard et al 2011;Weiland et al 2016), mechanosensitive Ca 2+ -permeable channels (MC) (Nakagawa et al 2007;Kurusu et al 2013;Hamilton et al 2015), and two-pore channels (TPC) (Peiter et al 2005;Patel et al 2016) have been cloned and characterised for their Ca 2+ conducting activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ signalling is a key topic in cell signalling research (Spalding and Harper 2011;Edel and Kudla 2014) and Eukaryotic cells generate cytosolic Ca 2+ signals via Ca 2+ -permeable channels. In plants, cyclic nucleotidegated cation (CNGC) channels (Frietsch et al 2007;Gao et al 2014Gao et al , 2016Chen et al 2015b), glutamate-like receptor (GLR) calcium channels (Michard et al 2011;Weiland et al 2016), mechanosensitive Ca 2+ -permeable channels (MC) (Nakagawa et al 2007;Kurusu et al 2013;Hamilton et al 2015), and two-pore channels (TPC) (Peiter et al 2005;Patel et al 2016) have been cloned and characterised for their Ca 2+ conducting activities.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one conserved CNGCs have been identified in pear (Pyrus bretschneideri Rehd.) (Chen et al 2015b) and Arabidopsis CNGCs have been identified as multi-functional regulators with roles in abiotic stress responses, pathogen defences, and reproductive fertility (Gao et al 2016;Jha et al 2016). GLRs act as sensors and mediators of numerous exogenous and endogenous signalling pathways in plants and animals (Weiland et al 2016) and have been associated with systemic wound responses, mitochondria and chloroplast functions, pollen tube growth, root apical meristem regulation, abscisic acid biosynthesis, water balance, carbon/ nitrogen sensing, and root development (Forde 2014;Teardo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all potential ZjCNGC genes were confirmed by HMMER analysis, which contains both the CNBD [cNMP_binding family (PF00027)] and the ion transport protein domain [ITP, Ion_trans family (PF00520)] [13,14]. The protein sequences with six membrane-spanning regions, a pore region, a CNBD, a CaMBD or an IQD were recognized as ZjCNGC proteins [15].…”
Section: Identification Of Cngc Genes In Chinese Jujubementioning
confidence: 93%
“…With informatics studies, the CNGC gene family has been identified in various plants; 20 members have been identified in Arabidopsis [4], 16 in rice [13], 18 in tomato [14], 21 in pear [15], 47 in wheat [16], 35 in tobacco [17], 12 in maize [18] and 26 in Brassica oleracea [19]. However, little is known about the biological information of the CNGC family in Chinese jujube.…”
Section: Introductionmentioning
confidence: 99%
“…The first plant CNGC was identified in Hordeum vulgare and named HvCBT1 (Schuurink et al 1998). The use of bioinformatics tools has led to the identification of the CNGC gene family members in Arabidopsis (20), rice (16) and other plants (18 in tomato and 26 in Brassica oleracea) (Bridges et al 2005;Nawaz et al 2014;Ward et al 2009;Zelman et al 2012;Saand et al 2015a;Chen et al 2015;Zelman et al 2013;Guo et al 2017;Kakar et al 2017). Manuscript to be reviewed have been characterized by genetic methods.…”
Section: Introductionmentioning
confidence: 99%